Assessing the Environmental Sustainability Corridor: Carbon Emissions in Relation to Gold Price, Economic Growth, Foreign Direct Investment, and Renewable Energy Consumption - Mehdi Seraj; Ayantayo Rukayat Olaide (Standards)
The growing concerns about global warming and its perceived influence on economic sustainability require a reassessment of the environmental consequences of gold mining, with a special focus on BRICS countries: Brazil, Russia, India, China, and South Africa. This paper examines the environmental sustainability corridor, carbon emission, gold price, economic growth, foreign direct investment (FDI), and renewable energy use between 1989 and 2020. The long-run association among the variables is checked by us through the PMG technique. Our findings indicate that while the gold price, FDI, and renewable energy use decrease carbon emission, economic growth adds to the increase in carbon emissions in the long run. These findings bring out the dual challenge of promoting economic growth while managing environmental impact. The study underlines how policymakers need to provide regulatory frameworks which will encourage renewable energy and responsible foreign investment, as a means of trying to mitigate the environmental impacts of gold mining and achieve sustainable development. Our research adds to the continuing debate about how economic expansion can be balanced with environmental preservation for resource-rich countries.